Bibliometric Analysis of Sustainable Packaging and Brand Communication - Judijanto, Loso (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of the scholarly landscape on sustainable packaging and brand communication, aiming to uncover key research themes, intellectual structures, and emerging trends in the field. Using data from the Scopus database and visualized through VOSviewer, a total of 350 publications were analyzed to identify patterns in keyword co-occurrence, author collaboration, and international research networks. The results reveal a significant evolution from early research focused on environmental impact and packaging materials toward more consumer-oriented themes, such as purchase intention, social media engagement, and eco-friendly brand messaging. Central concepts such as “sustainable development” and “sustainable packaging” dominate the literature, while emerging topics like “sustainable consumption” and “circular economy” reflect the growing integration of environmental and behavioral approaches. The United States, China, and the Netherlands emerge as major contributors in global collaboration networks. This study provides theoretical insight into the interdisciplinary nature of the topic and offers practical implications for marketers, policymakers, and sustainability strategists. Despite limitations related to database scope and content depth, this bibliometric mapping contributes valuable direction for future research and cross-sector innovation.